Berjasa Information System Sdn. Bhd. V Tan Gaik Leong (T/A Jurukur Berjasa) & Anor.: Case Note - Zainol, Zinatul A (Journal of Malaysian and Comparative Law, 1999)
The High Court of Kuala Lumpur delivered the first decision in Malaysia that estoppel is applicable in copyright. In Berjasa Information System Sdn. Bhd. V Tan Gaik Leong (T/A Jurukur Berjasa) & Anor (hereafter referred to as the 'Berjaya' case), the court held that the conduct of the defendants and their act of silence had estopped them from claiming ownership of the copyright.